Saccharomyces Cerevisiae Var Boulardii CNCM I-1079 Reduces Expression of Genes Involved in Inflammatory Response in Porcine Cells Challenged by Enterotoxigenic E. Coli and Influences Bacterial Communities in an In Vitro Model of the Weaning Piglet Colon - Raphaële Gresse; Juan J. Garrido; Angeles Jiménez-Marín; Sylvain Denis; Tom Van de Wiele; Evelyne Forano; Stéphanie Blanquet-Diot; Frédérique Chaucheyras-Durand (MDPI AG, 2021)
Enterotoxigenic Escherichia coli (ETEC) is the main infectious agent responsible for piglet post-weaning diarrhea with high mortality rates. Antimicrobials represent the current principal strategy for treating ETEC infections in pig farms, but the occurrence of multi-resistant bacterial strains has considerably increased in the last decades. Thus, finding non-antibiotic alternatives becomes a real emergency. In this context, we investigated the effect of a live yeast strain, Saccharomyces cerevisiae var boulardii CNCM I-1079 (SB) in an in vitro model of the weaning piglet colon implemented with a mucus phase (MPigut-IVM) inoculated with ETEC and coupled with an intestinal porcine cell line IPI-2I. We showed that SB was able to modulate the in vitro microbiota through an increase in Bacteroidiaceae and a decrease in Prevotellaceae families. Effluents collected from the SB treated bioreactors were able to mitigate the expression level of genes encoding non-gel forming mucins, tight junction proteins, innate immune pathway, and pro-inflammatory response in IPI-2I cells. Furthermore, SB exerted a significant protective effect against ETEC adhesion on porcine IPEC-J2 intestinal cells in a dose-dependent manner and showed a positive effect on ETEC-challenged IPEC-J2 by lowering expression of genes involved in pro-inflammatory immune responses. Our results showed that the strain SB CNCM I-1079 could prevent microbiota dysbiosis associated with weaning and protect porcine enterocytes from ETEC infections by reducing bacterial adhesion and modulating the inflammatory response.